Knowledge of HPV and HPV vaccine and its association with vaccination willingness among female undergraduates: A comparative cross-sectional study between healthcare and non-healthcare majors in Chengdu, China - Miao Zhao; Jing Lei; Qin Feng; Shan Lai; Qiong Liang; Min Xie (PLoS ONE, 2026)
Purpose This study aimed to assess levels of knowledge about human papillomavirus (HPV) and its vaccine among female undergraduates compare these levels between healthcare and non-healthcare majors, and examine their associations with vaccination willingness. Methods A cross-sectional survey was conducted among 1,293 female undergraduate students from two universities in Chengdu. Knowledge was measured using a self-designed questionnaire, categorized into basic and advanced domains. Vaccination willingness was assessed via a 5-point Likert scale. Data were analyzed using descriptive statistics, t-tests, analysis of variance and hierarchical multiple regression to identify associations and compare the two student groups. Results A total of 1191 valid questionnaires were analyzed. Participants demonstrated moderate basic knowledge of HPV (mean score = 5.21 ± 1.91/8) and its vaccine (mean score = 2.99 ± 1.05/5), but low advanced knowledge of HPV (mean score = 1.02 ± 1.03/6) and its vaccine (mean score = 2.00 ± 1.53/6). Students in healthcare majors demonstrated significantly higher scores in HPV basic knowledge (p = 0.023),HPV vaccine basic knowledge (p = 0.012), and advanced HPV vaccine knowledge (p < 0.001) compared to their non-healthcare peers. Overall vaccination willingness was higher among healthcare majors (p = 0.011), students from urban areas (p < 0.001), and those with higher monthly living expenses (p < 0.001). Hierarchical multiple regression analysis revealed that higher scores in basic knowledge were significantly associated with greater vaccination willingness (p < 0.001, △R 2 = 0.127). Conclusions The study confirms a significant knowledge and intention gap between healthcare and non-healthcare students. Basic knowledge of HPV and its vaccine acts as an effective peripheral cue that boosts vaccination willingness, aligning with the Elaboration Likelihood Model (ELM). However, widespread deficits in advanced knowledge, even among healthcare students, impede central-route processing and durable attitude formation. Public health efforts should prioritize clear core messaging while simplifying and disseminating advanced knowledge to narrow knowledge gaps across student students with different academic backgrounds.